Digital Technology and Socio-Dynamic Aspects of Indonesian Islamic Religious Education: A Total Quality Management Perspective - Zakiyyah, Intan; Suparto, Suparto; Karo-Karo, Imron Azhari; Zakir, Muhammad Nur Ahsan (Graduate School of Syarif Hidayatullah State Islamic University Jakarta, 2024)
The management of Islamic education learning based on digital technology, adapts to Islamic values, recognizing that religious education cannot rely solely on digital tools. Therefore, teachers still play a guiding role in providing direct support to students. This research aims to analyze the management of digital technology use in Islamic Religious Education (PAI) Total Quality Management Perspective. The findings indicate that character-based PAI learning through digital technology encompasses four key elements: digital teaching modules and Learning Management Systems (LMS), digital technology-based learning infrastructure, teacher training, and support for character development in students. These four elements are accompanied by total quality management, so that PAI learning using digital technology accelerates the achievement of educational goals. This research is qualitative, descriptive, and analytical, utilizing a phenomenological approach. Primary data for this research was obtained directly from the Islamic Development Network (IDN) in Bogor.